(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article analyzes the real aggregate income of the population, the real growth rate of aggregate income per capita and the volume of total disposable income of the population in the field of improving food security in Uzbekistan. In addition, work is underway to modernize Uzbekistan’s agriculture, study the factors influencing rising meat prices, analyze meat prices in foreign countries, and address problems with meat product supplies to ensure food security in Uzbekistan. At the same time, issues of reducing production costs and ensuring food security for our country were scientifically analyzed.